At the heart of education: Re-conceptualising the idea of care in pre-school services - Ilaria Mussini (Encyclopaideia)
If education is a process that is in relation to what is essential and necessary to life (cf. Luigina Mortari), it becomes critical to understand how schools, and in particular, pre-schools can be characterised as places of concrete expression of care, despite the fact that many international educational policies in ECEC (Early Childhood Education and Care) contexts pay little attention to this paradigm, relegating care to a secondary position, misrecognising its value as an ontological dimension of the human being. This article presents the preliminary phase of a phenomenologically-oriented qualitative research. Its object is the process of review of the international literature. This process was carried out through a scoping review aimed at mapping the key concepts and the main empirical studies, starting from the following broad review question: “What is care?”. The analysis brings out some conceptualisations of care and some nodes that characterise the relationship between care and education in ECEC contexts.